PENGARUH DAYA TARIK WISATA DAN ACARA JAMUAN MAKAN MALAM G20 INDONESIA TERHADAP KEPUTUSAN BERKUNJUNG KEMBALI KE GARUDA WISNU KENCANA, BALI - Pramesti, Dinar Sukma; Febriana, Febriana; Halim, Deddy Kurniawan (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2024)
In 2022, Bali was chosen as the venue for the G20 Indonesia Summit. Several activities were carried out, one of which was a dinner entitled 'Welcoming Dinner and Cultural Performance G20 Indonesia.' This event took place at the Garuda Wisnu Kencana (GWK) tourist destination. The research aims to determine the influence of the tourist attraction components at GWK on tourists' decisions to revisit Garuda Wisnu Kencana in Bali. This research is a mixed-method study that employs statistical analysis techniques using SPSS. The respondents included 50 domestic tourists who had previously visited GWK. The research results indicate that the tourist attraction of G20 Indonesia has a significant and positive influence on the decision to return to GWK. However, the tourist attraction component does not have a significant and positive effect on the decision to revisit GWK. It is hoped that this research can provide insights for tourist destination managers to identify the factors that influence tourists decisions to revisit a tourist destination.